Preliminary antenna system design for FMCW avalanche radar - Mohd. Isa, Farah Nadia; Ash, Matthew; Brennan, P.V. (IEEE, 2011)
This paper described the design and construction of a preliminary microstrip array antenna at 5.3 GHz. The antenna is going to be applied to an FMCW avalanche radar. The antenna design which composed of an array of 4 × 2 patches could achieve the high gain of 15.6 dB with a wideband of 90%. The high gain and wideband attributes is also achieved by separating the feed network from the main patches and increasing the antenna height. In order to ensure the power is transferred smoothly from the main input port, the feed network is designed in a nover spider-like tapered feed while ensuring the antenna performance is not affected.